The effect of monetary policy on income inequality: Empirical evidence from Asian and African developing economies - Zulfiqar Khan; Muhammad Azam Khan (Journal of Central Banking Theory and Practice, 2023)
Inequality is a challenging issue for all developing coun-tries across the globe. Evaluating the role of monetary policy in miti-gating inequality is imperative for researchers and policy makers.The central objective of the present study is to empirically evaluatethe impact of monetary policy on income inequality for ten Asianand African developing economies from 1990-2020. The methodsof pooled mean group (PMG)/panel autoregressive distributed lag(ARDL), and fully modified least square (FMOLS) are implemented.The empirical results indicate that money supply has negative, andinflation has a positive and significant influence on income inequal-ity. It has also been found that GDP per capita income and inwardforeign direct investment (FDI) have a negative impact on inequality.The findings of the present study recommend that money supply, percapita income, and inward FDI should be enhanced, while inflationmust be controlled using coordinated fiscal and monetary policies.
Keywords: E00; E25; C33; 330; Monetary policy; income inequality; panel ARDL; Asianand African countries